Modelling the Requirements of Rich Internet Applications in WebRe - Robles Luna, Esteban (2010)
In the last years, several Web methodological approaches were defined in order to support the systematic building of Web software. Together with the constant technological advances, these methods must be constantly improved to deal with a myriad of new feasible application features, such as those involving rich interaction features. Rich Internet Applications (RIA) are Web applications exhibiting interaction and interface features that are typical in desktop software. Some specific methodological resources are required to deal with these characteristics. This paper presents a solution for the treatment of Web Requirements in RIA development. For this aim we present WebRE+, a requirement metamodel that incorporates RIA features into the modelling repertoire. We illustrate our ideas with a meaningful example of a business intelligence application.